2011
DOI: 10.1021/nn2019286
|View full text |Cite
|
Sign up to set email alerts
|

Size-Selective Incorporation of DNA Nanocages into Nanoporous Antimony-Doped Tin Oxide Materials

Abstract: A conductive nanoporous antimony-doped tin oxide (ATO) powder has been prepared using the sol-gel method that contains three-dimensionally interconnected pores within the metal oxide and highly tunable pore sizes on the nanoscale. It is demonstrated that these porous materials possess the capability of hosting a tetrahedral-shaped DNA nanostructure of defined dimensions with high affinity. The tunability of pore size enables the porous substrate to selectively absorb the DNA nanostructures into the metal oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Mesoporous ATO films were synthesized on fluorine-doped tin oxide coated glass slides (FTO) using a sol-gel method (Experimental details can be found in the supplementary information). 16,17 As shown in Fig. 1, the resulting coatings are uniform and optically transparent.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Mesoporous ATO films were synthesized on fluorine-doped tin oxide coated glass slides (FTO) using a sol-gel method (Experimental details can be found in the supplementary information). 16,17 As shown in Fig. 1, the resulting coatings are uniform and optically transparent.…”
mentioning
confidence: 79%
“…Additionally, procedures for synthesizing nanoporous powders and films with accessible pores have been recently reported. 15,16 With respect to interaction with biomolecules, Simmons and coworkers recently demonstrated that DNA nanostructures can be adsorbed into porous ATO with retention of structure. 16 In this report, we demonstrate that two different model redox proteins, the hemoprotein cytC and the blue copper protein azurin, can be adsorbed in thin films of highly mesoporous ATO with retention of electron transfer functionality.…”
mentioning
confidence: 99%
“…However, the application of DNA tetrahedrons might be increased if it was possible to build a complex of several tetrahedrons. This concept has only been realized by unspecific accumulation ( 18 20 ) and linear complex formation ( 21 ). In this study, we functionalized the tetrahedrons with specific stem-loop sequences located at the vertices of the tetrahedron to allow specific complex formation enabled by kissing-loop interaction of the single-stranded loops.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the challenges and potential applications, there have been no reported examples of two dimensional (2D) DNA nanostructures encapsulation by artificial well-defined MOFs, let alone three dimensional (3D) DNA nanostructures2627. Here, we report a new composite material which is self-assembled from 3D DNA (guest) and pre-synthesized MOFs (host) in a well-dispersed fashion by electrostatic interactions and hydrophilic interactions.…”
mentioning
confidence: 97%